The state of public strategic management research: A selective literature review and set of future directions - Bryson, John M.; Yang, Kaifeng; Berry, Frances S. (2010)
Strategic planning and related strategic management elements have become ubiquitous practices at all levels of U.S. government and many nonprofit organizations over the past 25 years. The authors review strategic planning and management research over that time period using the premises of practice theory to guide the discussion. The review is organized according to 10 research directions proposed by Bryson, Freeman, and Roering (1986). Important gains have been made in a number areas, but much more remains to be done. The authors also propose four new research directions, including the need to (1) attend more fully to the nature of strategic management practice, (2) focus on learning and knowledge management generally as part of strategic management, (3) focus specifically on how strategy knowledge develops and is used, and (4) understand how information and communication technologies can be best integrated into strategic management. The fruits of further concentrated research can be improved public strategic management practice, including enhanced organizational capacity for addressing current and future challenges and improvements in long-term performance. - Reproduced.
Keywords: Public administration